Opinions of African American adults about the use of apolipoprotein L1 (ApoL1) genetic testing in living kidney donation and transplantation. Issue 3 (29th August 2020) - Berrigan, Margaret; Austrie, Jasmine; Fleishman, Aaron; Tercyak, Kenneth P.; Pollak, Martin R.; Pavlakis, Martha; Rohan, Vinayak; Baliga, Prabhakar K.; Kayler, Liise K.; Feeley, Thomas H.; Rodrigue, James R.
Abstract : Apolipoprotein L1 (ApoL1) predictive genetic testing for kidney disease, and its emerging role in transplantation, remains controversial as it may exacerbate underlying disparities among African Americans (AAs) at increased risk. We conducted an online simulation among AAs (N = 585) about interest in ApoL1 testing and its cofactors, under 2 scenarios: as a potential living donor (PLD), and as a patient awaiting transplantation. Most respondents (61%) expressed high interest in genetic testing as a PLD: age ≥35 years (adjusted odds ratio [aOR], 1.75; 95% confidence interval [CI], 1.18, 2.60, P  = .01), AA identity (aOR, 1.67; 95% CI, 1.02, 2.72, P  = .04), perceived kidney disease risk following donation (aOR, 1.68; 95% CI, 1.03, 2.73, P  = .03), interest in genetics (aOR, 2.89; 95% CI, 1.95, 4.29, P  = .001), and genetics self‐efficacy (aOR, 2.38; 95% CI, 1.54, 3.67, P  = .001) were positively associated with ApoL1 test interest. If awaiting transplantation, most (89%) believed that ApoL1 testing should be done on AA deceased donors, and older age (aOR, 1.85; 95% CI, 1.03, 3.32, P  = .04) and greater interest in genetics (aOR, 2.61; 95% CI, 1.41, 4.81, P  = .002) were associated with interest in testing deceased donors. Findings highlight strong support for ApoL1 testing in AAs and the need to examine such opinions among PLDs and transplant patients to enhance patient education efforts. Abstract : In a national online simulation survey study of African Americans, most express high interest in apolipoprotein L1 genetic testing as a potential living kidney donor, feel that potential living donors with high‐risk genotypes should not be excluded from donation in the absence of other contraindications, and believe that testing should be done on deceased donors with recent African ancestry.